The role of administrative digitization in supporting future entrepreneurs – An applied study on Asir Region, KSA – - Hassan, Abdul-Rahman Hassan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at identifying the reality of applying administrative digitization and its role in supporting future entrepreneurs in the Kingdom of Saudi Arabia. The study’s importance stems come from that administrative digitization is a newly established management approach to supports future entrepreneurs. The study adopted the descriptive-analytical approach, and used the questionnaire as a tool for the study, and was applied to a sample of future entrepreneurs amounting to (217) individuals who were chosen randomly. The results of the study found a statistically significant effect at the level of (0.05) for managerial digitization on supporting future entrepreneurs in entrepreneurial projects. To enhance the application of administrative digitization in entrepreneurial projects because of its positive effects on supporting future leaders, to develop plans and programs to benefit from them, and to establish a mechanism to stimulate the participation of future entrepreneurs to support and enhance efforts aimed at creating an organizational environment.